Regulatory pattern of abnormal promoter CpG island methylation in the glioblastoma multiforme classification - Wang, Rendong; Zhao, Lei; Wang, Shijia; Zhao, Xiaoxiao; Liang, Chuanyu; Wang, Pei; Li, Dongguo (Frontiers in Genetics, 2022)
Glioblastoma (GBM) is characterized by extensive genetic and phenotypic heterogeneity. However, it remains unexplored primarily how CpG island methylation abnormalities in promoter mediate GBM typing. First, we presented a multi-omics scale map between GBM sample clusters constructed based on promoter CpG island (PCGI) methylation-driven genes, using datasets including methylation profiles, expression profiles, and single-cell sequencing data from multiple highly annotated public clinical cohorts. Second, we identified differences in the tumor microenvironment between the two GBM sample clusters and resolved key signaling pathways between cell clusters at the single-cell level based on comprehensive comparative analyses to investigate the reasons for survival differences between two of these clusters. Finally, we developed a diagnostic map and a prediction model for GBM, and compared theoretical differences of drug sensitivity between two GBM sample clusters. In summary, this study established a classification system for dissecting PCGI methylation heterogeneity in GBM and provides a new perspective for the diagnosis and treatment of GBM.